Effectiveness of nursing interventions to prevent adverse reactions to iodinated cotrast media: systematic review protocol - dos Reis Presses Augusto, Renata Aparecida (2020)
This review aimed to identify evidence available in the literature about nursing interventions to prevent adverse reactions to iodinated contrast media. The research question for this study – “How effective are nursing actions at preventing adverse reactions in patients who will receive iodinated contrast?” – is based on issues that involve patient safety regarding the risk of adverse events. Method: systematic review based on the Joanna Briggs Institute protocol, which provides for the formulation of a guiding question, definition of descriptors, participation of two reviewers, definition of inclusion and exclusion criteria for studies, definition of electronic databases, selection of studies , critical analysis of the articles and synthesis of the data with the recommendation of the degree of evidence. Expected results: survey of scientific evidence to prevent adverse responses to the iodinated contrast medium, as well as provide means for the safety of radiological nursing care.